Islamic Spiritual Approaches to Address Maladaptive Perfectionism Among Muslim University Students - Yuni Saffiyatina; Fitriah M. Suud (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Maladaptive perfectionism is characterized by setting extremely high self-standards and excessive criticism, leading to serious psychological consequences, including stress, academic burnout, procrastination, and anxiety. In this context, Islamic spiritual solutions, such as tawakkul (religious belief) and sabar (patience), are considered effective approaches to building mental resilience. This study aims to identify causal factors, analyze the impact of maladaptive perfectionism on mental health and academic motivation, and explore Islamic Religious Education students' strategies for overcoming these impacts. Using a phenomenological design with a qualitative approach, informants were selected through purposive sampling: five active fifth-semester students who experience maladaptive perfectionism and actively apply Islamic spiritual solutions. Data analysis was conducted using the Miles and Huberman model. Maladaptive perfectionism is driven by a balanced interaction between internal factors (high personal standards, fear of mistakes) and external factors (parental expectations/criticism, competitive campus pressure). The main impacts are high levels of stress and academic burnout, as well as procrastination. Maladaptive perfectionism in college students is triggered by multifactorial pressures, significantly disrupting psychological well-being. Islamic spiritual strategies (dhikr, prayer, worship) and understanding Islamic Religious Education (PAI) material on faith and morals have proven effective as adaptive coping mechanisms for developing self-compassion and self-acceptance. This suggests the need for holistic student mentoring interventions, focusing on mental and spiritual balance.